After the peak water: the increasing influence of rock glaciers on alpine river systems. Issue 21 (23rd July 2019) - Brighenti, Stefano; Tolotti, Monica; Bruno, Maria Cristina; Engel, Michael; Wharton, Geraldene; Cerasino, Leonardo; Mair, Volkmar; Bertoldi, Walter
Abstract: Human‐accelerated climate change is quickly leading to glacier‐free mountains, with consequences for the ecology and hydrology of alpine river systems. Water origin (i.e., glacier, snowmelt, precipitation, and groundwater) is a key control on multiple facets of alpine stream ecosystems, because it drives the physico‐chemical template of the habitat in which ecological communities reside and interact and ecosystem processes occur. Accordingly, distinct alpine stream types and associated communities have been identified. However, unlike streams fed by glaciers (i.e., kryal), groundwater (i.e., krenal), and snowmelt/precipitation (i.e., rhithral), those fed by rock glaciers are still poorly documented. We characterized the physical and chemical features of these streams and investigated the influence of rock glaciers on the habitat template of alpine river networks. We analysed two subcatchments in a deglaciating area of the Central European Alps, where rock glacier‐fed, groundwater‐fed, and glacier‐fed streams are all present. We monitored the spatial, seasonal, and diel variability of physical conditions (i.e., water temperature, turbidity, channel stability, and discharge) and chemical variables (electrical conductivity, major ions, and trace element concentrations) during the snowmelt, glacier ablation, and flow recession periods of two consecutive years. We observed distinct physical and chemical conditions and seasonal responses for the different stream types. Rock glacial streams were characterized by very low and constant water temperatures, stable channels, clear waters, and high concentrations of ions and trace elements that increased as summer progressed. Furthermore, one rock glacier strongly influenced the habitat template of downstream waters due to high solute export, especially in late summer under increased permafrost thaw. Given their unique set of environmental conditions, we suggest that streams fed by thawing rock glaciers are distinct river habitats that differ from those normally classified for alpine streams. Rock glaciers may become increasingly important in shaping the hydroecology of alpine river systems under continued deglaciation.